Hubungan Dukungan Suami dengan Kecemasan Wanita yang Mengalami Menopause di Dusun Karang Jati Sleman Yogyakarta - Ika Hermawati; Sri Arini Winarti; Dewi Ratnasari (LPPM STIKES Guna Bangsa, 2014)
Background: The husband's support was the most improved external factors in helping the wife to go through the menopause without excess anxiety.Support on women in the past through menoapuse in need of surrounding people especially the husband as life partner. Data of menopausal women a village Sleman Yogyakarta is 150 people. After a Screening at the time of the preliminary study in the village of Sleman Yogyakarta there are 60 women who are anxious. Aim: To know the relation between husband’s support with anxiety woman who had menopause in Karangjati Sleman, Yogyakarta Methods: This study used a survey of analytical research methods with cross sectional approach. The subject of this research is on 60 menopausal women. Data retrieval using guided questionnaire that have been tested by there searchers. Data analysis performed using Spearman Ranktest. Result: The husband's support in menopausal women in the category of poor numbered 25 persons (41.7%). The level of anxiety of menopausal women in the category of Weight numbered 39 persons (65%). Based on the results of statistical values P value = 0,014 (p<0.05), there is a relation between husband’ssupport with anxiety woman who had menopause in KarangJati Sleman,Yogyakarta Conclusion: There is a relation between husband’s support with anxiety woman who had menopause in Karang Jati, Sleman,Yogyakarta